A 3D peony-like sulfur-doped carbon nitride synthesized by self-assembly for efficient photocatalytic hydrogen production. (17th June 2021) - Fei, Ting; Qin, Chaochao; Zhang, Yiwei; Dong, Guomeng; Wang, Yanyun; Zhou, Yuming; Cui, Minghuan
Abstract: Photocatalytic hydrogen evolution reaction (HER) provides a new way for the development of clean energy. Herein, a high-performance peony-like 3D structure S-doped carbon nitride (SCNx) with a large specific surface area was synthesized through a universal and non-thermal polymerization template-free approach. As an additional component, the introduction of trithiocyanuric acid in the raw material led to the formation of supramolecular intermediates through hydrogen bond self-assembly, and the sulfur was introduced into the framework of g-C3 N4 subsequently. The charge separation lifetime of SCNx was studied by transient absorption spectroscopy, and the reason for its excellent optical performance was revealed from a dynamic perspective. Furthermore, the resulting SCNx composite material shows significant photocatalytic hydrogen release performance under visible light irradiation. In particular, the photocatalytic hydrogen rate of SCN1.0 reached 567.7 μmol/h, which was almost 53 times that of BCN, and was also 2.3 times that of SCN0 obtained by the binary self-assembly of melamine and cyanuric acid. Our finding advances the application of simple, environmentally friendly, and scalable strategy for the synthesis of high-performance sulfur-doped g-C3 N4 photocatalysts. Graphical abstract: Image 1 Highlights: A new template-free and low-cost self-assembly method was developed to prepare carbon nitride. The special 3D peony-like morphology ensures a large specific surface area and abundant reactive sites. The hydrogen production activity of SCN1.0 was up to 567.7 μmol/h, which can be explained by the TA spectroscopy.